Immune Modulatory Activities of Arginyl-Fructose (AF) and AF-Enriched Natural Products in In-Vitro and In-Vivo Animal Models - Jin-A Yu; Jung-Yun Lee; Tae Yang Kim; Hanna Kang; Su-Young Lee; Haimanot Mitiku; Joonheum Park; Young Hwan Lee; Hung-Bae Chang; Byung Ha Lee; Kichoon Lee; Emmanouil Apostolidis; et al. (Molecules, 2021)
The immune system plays an important role in maintaining body homeostasis. Recent studies on the immune-enhancing effects of ginseng saponins have revealed more diverse mechanisms of action. Maillard reaction that occurs during the manufacturing processes of red ginseng produces a large amount of Amadori rearrangement compounds (ARCs), such as arginyl-fructose (AF). The antioxidant and anti-hyperglycemic effects of AF have been reported. However, the possible immune enhancing effects of non-saponin ginseng compounds, such as AF, have not been investigated. In this study the effects of AF and AF-enriched natural product (Ginofos, GF) on proliferation of normal mouse splenocytes were evaluated in vitro and male BALB/c mice models. The proliferation of splenocytes treated with mitogens (concanavalin A, lipopolysaccharide) were further increased by addition of AF (p < 0.01) or GF (p < 0.01), in a dose dependent manner. After the 10 days of oral administration of compounds, changes in weights of spleen and thymus, serum immunoglobulin, and expression of cytokines were measured as biomarkers of immune-enhancing potential in male BALB/c mice model. The AF or GF treated groups had higher weights of the thymus (0.94 ± 0.25 and 0.86 ± 0.18, p < 0.05, respectively) than that of cyclophosphamide treated group (0.59 ± 0.18). This result indicates that AF or AF-enriched extract (GF) increased humoral immunity against CY-induced immunosuppression. In addition, immunoglobulin contents and expression of cytokines including IgM (p < 0.01), IgG (p < 0.05), IL-2 (p < 0.01), IL-4 (p < 0.01), IL-6 (p < 0.01), and IFN-γ (p < 0.05) were also significantly increased by supplementation of AF or GF. These results indicate that AF has immune enhancing effects by activation of adaptive immunity via increase of expression of immunoglobulins and cytokines such as IgM, IgG, IL-2, IL-4, IL-6 and thereby proliferating the weight of thymus. Our findings provide a pharmacological rationale for AF-enriched natural products such as ginseng and red ginseng that can possibly have immune-enhancement potential and should be further evaluated.